Exploring nominalization and lexical density deployed within research article abstracts: A grammatical metaphor analysis - Istiqomah, Faizatul; Basthomi, Yazid (Englisia Journal, 2024)
In research articles published for international reputable journals, the crucial role of abstracts to attract readers, especially reviewers or editors, is not in doubt. The article is expected to not experience direct desk rejection due to non-impressive and persuasive lexical choices in the abstract for further reading. This paper proposes a corpus study to scrutinize ideational grammatical metaphor (IGM) from the abstracts of successfully published articles in four applied linguistic quality indexed Scopus journals (Q1 and Q2) managed by Asian countries. The data were analyzed based on Halliday’s SFL framework focused on the realization of IGM in nominalization and lexical density. The pattern of IGM examined was on the transference of process and quality nominalization through morphological derivations. The findings show that the shift from process to thing dominates the other with many variations of suffixes within the words. In addition, the abstracts’ lexical density results ranged from 45 to 72 percent. Thus, it is suggested that English teachers consider raising students’ awareness of nominalization to produce lexically dense but informative texts in their academic writing classes.